Undergraduate Financial Stress, Financial Self-Efficacy, and Major Choice: A Multi-Institutional Study - Kevin Fosnacht; Shannon M Calderone (Journal of Financial Therapy, 2017)
Over time, undergraduates students been increasingly forced to assume a greater portion of college costs. For most students, this means borrowing larger sums and cutting back on expenses to fulfill their college dreams, which often leads to financial stress. Using financial self-efficacy theory, we sought to better understand how a lack of financial confidence and a diminished sense of financial well-being may serve to undermine students’ intended short and long-term goals. To this end, we examined the predictors of financial stress based upon a multi-institutional sample of senior undergraduates and focus on the role of the earnings potential of different majors.
Keywords: Financial stress; college students; major choice; self-efficacy